Ibn Al-Haythamâs Classification of Knowledge - Ishaq, Usep Mohamad; Wan Daud, Wan Mohd Nor (Al-Jamiah: Journal of Islamic Studies, 2017)
Ibn al-Haytham (d. 1039) is a well known scholar for his contributions in natural and mathematical sciences. The research focuses on his works in sciences and mathematics and only a few studies carry out on his contribution on philosophy due to the lack of the primary sources. The only known surviving Ibn al-Haythamâs work on philosophy is KitÄb Thamarah al-á¸¥ikmah. However, few studies have examined and explored this work. Based on this work, the present study tries to scrutinize Ibn al-Haythamâs epistemology and focused mainly on his classification of knowledge. The comparative study of Ibn al-Haythamâs classification of knowledge and that of al-FÄrÄbÄ«âs, Ibn á¸¤azmâs, á¹¬Å«sÄ«âs, and al-GhÄzÄlÄ«Â  is also carried out. The result shows that Ibn al-Haytham has two mode of classifications: the ontological and epistemological. It is also obvious that Ibn al-Haytham tries to integrate Greek philosophy and sciences within the worldview of IslÄm. The results of the present study also suggests that the nexus between the concept of classification of knowledge and the concept of perfect man (al-insÄn al-tÄmm) is obvious.[Ibn al-Haytham (w. 1039) adalah sarjana yang dikenal sumbangsihnya dalam ilmu-alam dan matematika. Penelitian-penelitian hingga saat ini cenderung difokuskan pada karya-karya sains dan matematikanya saja dan hanya sedikit dilakukan pada karya-karya filsafatnya karena kurangnya rujukan primer. Satu-satunya karya Ibn al-Haytham yang ada dalam bidang filsafat adalah KitÄb Thamarah al-á¸¤ikmah. Namun, studi yang dilakukan untuk meneliti dan mengeksplorasi karya ini sejauh ini amat kurang. Berdasarkan karyanya tersebut, kajian ini mencoba untuk meneliti dengan seksama epistemologi Ibn al-Haytham dan utamanya difokuskan pada klasifikasi ilmu pengetahuan. Studi perbandingan antara klasifikasi ilmu Ibn al-Haytham dengan al-FÄrÄbÄ«âs, Ibn á¸¤azmâs, á¹¬Å«sÄ«âs, and al-GhÄzÄlÄ« juga dihadirkan. Hasil penelitian menunjukkan bahwa Ibn al-Haytham memiliki dua cara klasifikasi ilmu pengetahuan. Juga sangat nampak bahwa Ibn al-Haytham mencoba memadukan filsafat dan sains Yunani dalam pandangan alam Islam. Kajian ini juga menunjukkan bahwa terdapat hubungan yang jelas antara konsep klasifikasi ilmu pengetahuan dengan konsep manusia sempurna (al-insÄn al-tÄmm)]